Smart contracts and personal data protection (Papeles, 2023)
Blockchain is an innovative technology that allows for a more efficient life for people, through a variety of actions, including enabling trustworthy transactions and reducing operating costs. In relation to Blockchain, Smart Contracts have emerged, revolutionizing the field of contracts. There are great expectations surrounding these technological advances for various sectors such as finance or registration. However, despite the obvious benefits, some obstacles are being identified regarding compliance with regulations on personal data protection in the service of smart contracts, specifically in relation to privacy/confidentiality controls and the right to be forgotten due to the governing principles of Blockchain.
Keywords: Smart Contracts; Personal Data Protection; Blockchain